PENGARUH RASIO KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN INDEKS LQ 45 BEI - Afifah Nur Laili; Aang Afandi; Fathimatus Zahro Fazda Oktavia (Politeknik Negeri Malang, 2022)
The purpose of this research is to analyze the effect of financial ratios and company size on the profit growth of companies listed on the Indonesia Stock Exchange LQ 45. The sample of this research is 26 out of 45 companies that enter LQ 45 for 2018-2020. The sample was selected using a purposive sampling technique. The statistical technique used in data analysis and hypothesis testing is multiple linear regression. Independent variables consist of profitability ratios (Net Profit Margin), liquidity ratios (Current Ratio), activity ratios (Total Asset Turnover), solvency ratios (Debt Equity Ratio), and company size. The results showed that only the profitability ratio had a significant and positive effect on profit growth. While the liquidity ratio, activity ratio, solvency ratio and firm size have no significant effect on profit growth. Furthermore, financial ratios and firm size simultaneously have a significant effect on profit growth.